Surface characterization of thiazolidinone derivatives by inverse gas chromatography - Fidan, Ismail; Dasdan, Dolunay Sakar; Karaman, Ferdane; Kaban, Seniz (BULGARIAN ACAD SCIENCE, 2017)
Inverse gas chromatography at infinite dilution was used for the first time to determine the adsorption properties and acid-base contributions to the surface energy of thiazoldin-4-ones bearing heteroaryl substituents. 3-(6-Methyl-2-pyridyl)-2-(2-thienyl)-1,3-thiazolidin-4-one (MPTT) and 3-(6-Methyl-2-pyridyl-2-(3-methyl-2-thienyl-1,3-thiazolidin-4-one (MPMTT) were freshly synthesized via one-pot three component condensation reaction. The retentions of nonpolar solvents such as n-hexane, n-heptane, n-octane, n-nonane, n-decane and other acidic, basic and amphoteric probes such as tetrahydrofurane, dichloromethane, chloroform, acetone and ethyl acetate used without further purification on MPTT and MPMTT were measured in the temperature ranges from 303 to 333 K by inverse gas chromatography (IGC). The dispersive component of the surface energy, gamma(D)(S) of studied adsorbent surface was estimated using retention times of different nonpolar organics in the infinite dilution region. Dispersive components of the surface energies, gamma(D)(S)according to Fowkes and Dorris-Gray approaches and the acid, K-A and base, K-D constants for the 3-(6-Methyl-2-pyridyl)-2-(2-thienyl)-1,3-thiazolidin-4-one and 3-(6-Methyl-2-pyridyl)-2-(3-methyl-2-thienyl-1,3-thiazolidin-4-one were calculated.
Keywords: Inverse gas chromatography; Thiazolidinone derivatives; Surface and adsorption properties; Surface free energies; Lewis acid-base constants; LIQUID-CRYSTAL; ACID-BASE; AGENTS; Chemistry